PENGGUNAAN MODEL CYCLE LEARNING DENGAN MEDIA GRAFIS UNTUK MENINGKATKAN PEMBELAJARAN IPS DI KELAS IV SDN 2 KLOPOSAWIT TAHUN AJARAN 2015/2016 - Dewi, Kikin (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Use of Cycle Learning Model Using Graphics Media in Improving Social Science Learning about Cooperation for the Fourth Grade Students of SDN 2 Kloposawit in the Academic Year of 2015/2016. The objectives of this research are to describe the use of Cycle Learning model using graphics media and to improve social science learning. This research is a collaborative Classroom Action Research (CAR) with subjects of fourth grade students of SD Negeri 2 Kloposawit. Data were analyzed using data reduction, data display, and drawing conclusion or verification. The results of this research showed that there are five steps of the use of Cycle Learning model using graphic media, namely: (a) engagement, (b) exploration, (c) explanation, (d) elaboration, and (e) evaluation using engagement, exploration, and explanation by using graphic media. Furthermore, the use of Cycle Learning using graphic media can improve social science learning. It was proven by the increase of students? learning outcomes in the first cycle 56.25%, in the second cycle 81.25%, and in the third cycle 92.75%. Keywords: Cycle Learning, graphic media, learning, social science Abstrak: Penggunaan Model Cycle Learning dengan Media Grafis untuk Meningkatkan Pembelajaran IPS tentang Koperasi di Kelas IV SDN 2 Kloposawit Tahun Ajaran 2015/2016. Tujuan dari penelitian ini adalah untuk mendeskripsikan penggunaan model Cycle Learning dengan media grafis dan meningkatkan pembelajaran IPS. Penelitian ini merupakan penelitian tindakan kelas kolaborasi dengan subjek siswa kelas IV SDN 2 Kloposawit. Analisis data menggunakan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penggunaan model Cycle Learning dengan media grafis dilakukan melalui lima langkah pembelajaran, yaitu (a) engagement, (b) exploration, (c) explanation, (d) elaboration, dan (e) evaluation dengan langkah engagement, exploration, dan explanation menggunakan media grafis. Selain itu, penggunaan model Cycle Learning dengan media grafis dapat meningkatkan pembelajaran IPS. Hal tersebut dapat dilihat dari peningkatan ketuntasan hasil belajar siswa pada siklus I 56,25%, siklus II 81,25%, dan siklus III 93,75%. Kata Kunci: Cycle Learning, media grafis, pembelajaran, IPS